Evaluation of the Manual Dexterity of Second-Year Dental Students after One Semester of Preclinical Training - Qashou, Manar; Mulhem, Hana; Aldweik, Deema; Najim, Noor; Uthman, Asmaa T.; Abdelmagied, Mawada; Aljafarawi, Tareq; Saeed, Musab; Al-Rawi, Natheer H. (European Journal of Dentistry, 2025)
Utilizing the Purdue Pegboard exam and the O'Connor exam, we assessed the impact of a semester-long preclinical training on the manual dexterity of dental students. Moreover, we examined the impact of gender, additional dental education, and practical exercises on manual dexterity.The study comprised a cohort of 45 preclinical students who were in their first year of dental school. The sample process was simple and convenient. Assessments were conducted at two distinct time points: T0, before the preclinical training laboratory, and T1, 7 months after the preclinical training laboratory. The Purdue Pegboard Test and the O'Connor Tweezer Dexterity Test were administered under identical conditions in both rounds of the trial. A validated survey was utilized to collect data on the gender, hands on activities, extra dental training, artistic skills, psychomotor skills, outdoor activities, and previous exposure to dental skills of each participant.The dental students in the study demonstrated a significant improvement in their manual dexterity skills from the dental simulation preclinical laboratory training (T0) to 7 months of laboratory training (T1). This improvement was measured using the Purdue Pegboard Test and the O'Connor Tweezer Dexterity Test, with statistical significance at p < 0.05. Females have a significantly higher score in the Purdue indirect visual test of the left hand than males. Students who dedicated extra time to dental training showed significant improvements compared with those who did not allocate extra time for training.This study emphasizes the importance of manual dexterity in dental education and its correlation with preclinical training, hands-on practice, and gender. The results indicate significant improvements in manual dexterity following one semester of preclinical training, with discernible differences between genders. The findings highlight the significance of practice and further training in improving manual dexterity skills in dental students. This suggests that there may be implications for the development of curriculum and admissions procedures in dental education.
Keywords: manual dexterity; Pegboard Test; O'Connor test; dental training